2022
DOI: 10.1101/2022.09.01.506196
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cellular senescence promotes progenitor cell expansion during axolotl limb regeneration

Abstract: Axolotl limb regeneration is accompanied by the transient induction of cellular senescence within the blastema, the structure which nucleates regeneration. The precise role of this blastemal senescent cell (bSC) population, however, remains unknown. Here, through a combination of gain- and loss-of-function assays, we elucidate the functions and molecular features of cellular senescence in vivo. We demonstrate that cellular senescence plays a positive role during axolotl regeneration, by creating a pro-prolifer… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 72 publications
1
4
0
Order By: Relevance
“…While we have not observed sustained, pro-proliferative effects specific to the muscle progenitors in the blastema (Figure 1h), it remains conceivable that senescent cells promote proliferation of additional blastema populations, which may explain the notable acceleration of blastema development observed upon senescent cell implantation (Figure 1b-d). This is in agreement with further data from our group (Yu et al, 2022), which reports that senescent cells facilitate progenitor cell expansion in the axolotl. Additionally, senescent cell clearance in salamanders is achieved by macrophages (Yun et al, 2015), raising the possibility that senescent cells may have indirect functions via recruitment or regulation of immune cell activity, important in other regenerative contexts (Ratnayake et al, 2021).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…While we have not observed sustained, pro-proliferative effects specific to the muscle progenitors in the blastema (Figure 1h), it remains conceivable that senescent cells promote proliferation of additional blastema populations, which may explain the notable acceleration of blastema development observed upon senescent cell implantation (Figure 1b-d). This is in agreement with further data from our group (Yu et al, 2022), which reports that senescent cells facilitate progenitor cell expansion in the axolotl. Additionally, senescent cell clearance in salamanders is achieved by macrophages (Yun et al, 2015), raising the possibility that senescent cells may have indirect functions via recruitment or regulation of immune cell activity, important in other regenerative contexts (Ratnayake et al, 2021).…”
Section: Discussionsupporting
confidence: 94%
“…Notophthalmus viridescens limb‐derived A1 cells (Ferretti & Brockes, 1988 ) and A1n gfp cells (Yun et al, 2015 ) were cultured as previously described (Yu et al, 2022 ; Oliveira et al, 2022 ); in brief, cells were grown on gelatin‐coated flasks in MEM (Gibco) supplemented with 2 nM L‐glutamine (Gibco), 10 μg/mL insulin (Sigma), 100 U/mL penicillin/streptomycin (Gibco), 10% heat‐inactivated FCS (Gibco) and 25% v/v dH 2 O. Cells were passaged 1:2 when approaching 70–80% confluence and maintained at 25°C and 2% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, activation of macrophages could help in clearing the fibrosis by a facilitated infiltration within proliferating new cardiac myocytes (32). Such a proliferative process for new cardiac progenitors emerging from a blastemal 9 could also be boosted by many p21+ senescent cells that we identified in our single cell-RNA seq dataset (Fig 6 ) as found during axolotl regeneration process (33).…”
mentioning
confidence: 78%
“…These cells are then cleared by macrophages after their recruitment (H. Li et al, 2021). In addition, recent work on axolotl limb regeneration has revealed that senescent cells create a pro‐proliferative niche for progenitor cell expansion and blastema outgrowth (Yu et al, 2022). Thus, cGAS‐STING activation and cGAS suppressor downregulation during regeneration promotes cell senescence while simultaneously creating an environment primed for immune cell recruitment and tissue remodeling.…”
Section: Discussionmentioning
confidence: 99%